23 PERFORMANCE OF BLOOD PRESSURE MEASUREMENTS TECHNIQUE AMONG GENERAL PRACTITIONERS IN THEIR WORK SETTINGS. (July 2018) - Fatah, Abraham; Pranata, Raymond; Wiharja, Wendy; Bertha,; Damay, Vito A.
Abstract : Objective: Measuring Blood Pressure (BP) seemed simple to do, yet it has many detailed aspects which are frequently missed in order to get the most accurate BP measurement. There are several things to do to avoid overestimation or underestimation of BP measurement. This study aimed to describe about how many aspects that General Practitioners applied while measuring BP and how much measurements taken before diagnosing someone with hypertension. Method: Online Questionnaire was created using Google Sheet Form, link: This link was broadcasted using LINE, WhatsApp, and BBM application as media tagged with "for general practitioner only". Simple randomized sampling was used. There were 55 respondents (20 males, and 35 females). Data were then analyzed using SPSS 23. Result: Out of 57 respondents, consist of GPs, only 13 respondents (22.8%) who did well measuring BP (applied 13–15 out of 15 aspects). 17 respondents (29.8%) did quite well while measuring BP (applied 10–12 out of 15 aspects). 27 respondents (47.4%) did poorly while measuring BP (applied <10 out of 15 aspects). There are 4 respondents who measured BP 1x for diagnosing hypertension, 30 respondents who measured BP 2x for diagnosing hypertension and 21 respondents who measured 3 times or more. Conclusion: Almost half of the respondents did poorly while measuring BP, and most of respondents measured at least 2 times before diagnosing hypertension which is in alignment with guidelines. This condition may be caused by many things such as: not enough time while measuring BP, patient is not compliant, lack of detailed knowledge about BP measurement, etc. Although GP suffered hardship while measuring BP, we encourage all GPs to do his/her best while measuring patient's BP, for patient's welfare.